2007
DOI: 10.1108/00242530710818018
|View full text |Cite
|
Sign up to set email alerts
|

Cultural issues, organizational hierarchy and information fulfilment

Abstract: Article Type: Conceptual paper Purpose of this paper: This paper presents the cultural results of a three year study into the concept of information fulfilment and considers the impact of culture on levels of information fulfilment.Design/Methodology/Approach: Ethnographic studies were undertaken within higher education institutions in four countries, by examining each organisation's shape and comparing it with the level of achievement of information fulfilment. The social and symbolic meanings that underpinne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…For instance, contrary to previous studies which noted lack of time as a prominent barrier (Ling et al, 2007;Riege, 2005;Santos et al, 2012), it was rated very low in this study (mean = 3.39). This was therefore, a positive outcome and showed their willingness to be part of any KS initiativesdespite the busy hospital schedules.It also showed that team work,which required time to be together,can flourish among them (Burke, 2007). Another surprising outcome was that more than half (52.2%) of respondents did not see "knowledge is power"as a serious hindrance.…”
Section: Individual Barriers To Ksmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, contrary to previous studies which noted lack of time as a prominent barrier (Ling et al, 2007;Riege, 2005;Santos et al, 2012), it was rated very low in this study (mean = 3.39). This was therefore, a positive outcome and showed their willingness to be part of any KS initiativesdespite the busy hospital schedules.It also showed that team work,which required time to be together,can flourish among them (Burke, 2007). Another surprising outcome was that more than half (52.2%) of respondents did not see "knowledge is power"as a serious hindrance.…”
Section: Individual Barriers To Ksmentioning
confidence: 99%
“…However, a previous study by Sandhu et al (2011) had noted that lack of trust was not a serious individual barrier for public servants, as it was scored lowest in their study. The recognitionof trust as a major barrier was consistent with theearlier assertion by respondents on colleague's willingness to share knowledge.It also implicated the multicultural make-up of the hospital (McLaughlin et al, 2008;Burke, 2007).Furthermore, itshowed that they believed that the coordination and interaction among departments in the hospital were important and inevitable in the overall management of patientsirrespective of the diverse backgrounds (Hofstede and Hofstede, 2005). It was interesting to note that there was significant difference in the perception of the medical and non-medical staffs on both items (Table 4).…”
Section: Individual Barriers To Ksmentioning
confidence: 99%
See 1 more Smart Citation
“…All the relatively new "free" Eastern European societies have in common a sense of uncertainty about the future and this aspect has important consequences regarding the need to share and trust information. Uncertainty can be viewed from two areas, that of "relational uncertainty" (according to Berger, 1975) where it is difficult for employees to predict the beliefs and behaviour of colleagues and the that of "informational uncertainty" where the accuracy of the actual information is called into question -as addressed in the information seeking literature (Burke, 2003(Burke, , 2006(Burke, , 2007Choo 2001;Kuhlthau, 1993;Davenport and Prusak;. Both these areas are concerned with three issues.…”
Section: Societal Influencesmentioning
confidence: 99%
“…Uncertainty can be viewed from two areas, that of "relational uncertainty" (according to Berger, 1975) where it is difficult for employees to predict the beliefs and behaviour of colleagues and the that of "informational uncertainty" where the accuracy of the actual information is called into question -as addressed in the information seeking literature (Burke, 2003(Burke, , 2006(Burke, , 2007Choo 2001;Kuhlthau, 1993;Davenport and Prusak;. Both these areas are concerned with fear and trepidation experienced by organisational members about levels of accuracy, quantity of information -if there is sufficient knowledge to make quality decisions and issues about trusting the source of the information.…”
mentioning
confidence: 99%